2020
DOI: 10.5430/ijhe.v9n6p1
|View full text |Cite
|
Sign up to set email alerts
|

EFL Students Perspective towards Online Learning Barriers and Alternatives Using Moodle/Google Classroom during COVID-19 Pandemic

Abstract: Covid-19 pandemic has made many countries adapt on new situations in different sectors including education. The Indonesia government has decided to adjust the education mode from face-to-face to online meeting using various learning management systems (LMS) such as moodle and google classroom. Moreover, the present research depicted the online learning barriers faced by students as well as their alternatives to cope them. The research implemented descriptive mixed-method survey design. The participants were 25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
192
0
19

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(226 citation statements)
references
References 7 publications
15
192
0
19
Order By: Relevance
“…In addition, similar story was reported by private newspaper the Bhutanese (Seldon, 2019). This finding also corroborates with Octaberlina and Muslimin (2020) who reported that students of Indonesia experienced three barriers during online learning which includes unfamiliarity of e-learning, slow internet connection and physical condition e.g. eye strain.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, similar story was reported by private newspaper the Bhutanese (Seldon, 2019). This finding also corroborates with Octaberlina and Muslimin (2020) who reported that students of Indonesia experienced three barriers during online learning which includes unfamiliarity of e-learning, slow internet connection and physical condition e.g. eye strain.…”
Section: Discussionsupporting
confidence: 90%
“…As a result, learning becomes very ineffective because they have to go in and out from the system and more often when they leave the system it would be very difficult to log in again. It is in line with the result study of Octaberlina and Muslimin (2020) which stated the lack of internet became a main barrier in implementing e-learning.…”
Section: Discussionsupporting
confidence: 86%
“…From the other side, as Octaberlina and Muslimin [13] point out, students had to be creative to find any solutions and innovations regarding learning barriers including maintaining good communication with teacher and understanding the best learning styles individually.…”
Section: Discussionmentioning
confidence: 99%
“…), but the consequences of this transition are not always transparent. For example, the barriers to online learning that students face are described by Octaberlina and Muslimin [7]. The results of their research showed that students experienced three barriers during online learning including unfamiliarity of e-learning, slow internet connection, and physical condition e.g.…”
Section: Introductionmentioning
confidence: 99%